Współpraca USA–ZSRR w zakresie repatriacji amerykańskich jeńców wojennych w latach 1944–1947 - Arkusz, Aleksandra (Kwartalnik Historyczny, 2014)
US–USSR Cooperation concerning the Repatriation of American POWs in the 1944–1947 Period An American-Soviet agreement regulating the principles of the mutual repatriation of POWs and civilians liberated from German captivity by the military units of both states was signed at the Yalta Conference (11 February 1945). Repatriation was entrusted to the USA Military Mission in the USSR, headed by Major General John R. Deane and the Plenipotentiary Council of Peoples’ Commissars / Council of Ministers of the USSR on Matters of Repatriation headed by Colonel General Filipp Ivanovich Golikov. In 1945–1947 the Plenipotentiary Board repatriated 22 481 American citizens via a transit camp in Odessa, and from May 1945 – directly across the front line. Despite the signed agreement the Soviet side did not respect its fundamental decisions, the most important of which pertained to the establishment of contact teams (officers active in the liberated camps and POW gatherings), to which the Soviet authorities refused to agree. Furthermore, the prime problems included: lack of consent for supplying food and medicines to units containing American citizens, hampering the evacuation of the sick and the wounded, failure to inform the American side about the localisation of the liberated camps and the number of inmates-USA citizens, as well as the absence of suitable organisational efforts on the part of the USSR albeit formulated in the agreement. Repatriation was additionally hindered by the limited funds of the Plenipotentiary Board, the absence of a clear-cut division of competence, and rivalry between particular Soviet ministries.